Transformation of the Architecture of the City as an Impact of the Presence of University Campuses in Depok - Prasidha, I Nyoman Teguh; Martokusumo, Widjaja; Lubis, Basauli Umar (Center for Research and Community Services ITB, 2019)
The presence of a university in a city not only affects the activities of its citizens but also its physical environment. The establishment of a number of university campuses at the end of the 1980s in Depok caused a significant transformation of the architecture of the city. This paper focuses on the process and pattern of the transformation of the architecture of Depok city that have occurred in the areas surrounding the university campus, and the effect on its physical environment. The method of urban typo-morphology study was used to investigate the transformation process and pattern of transformation in the study location and the factors influencing them and their effect on the quality of the physical environment. This research revealed that the existence of university campuses had multiple effects on the physical environment of their surrounding areas. Uncontrollable changes in the elements of the architecture of the city have caused various unsafe conditions and a decline in the quality of its physical environment. The result of this research can be applied to deal with changes in the physical environment around the university campuses, and also for comparison to other cities with similar cases. Abstrak. Keberadaan universitas di suatu kota tidak hanya mempengaruhi kegiatan warganya, tetapi juga lingkungan fisiknya. Kehadiran beberapa kampus universitas pada akhir 1980-an di Depok, secara signifikan menyebabkan transformasi arsitektur kota. Makalah ini berfokus pada proses dan pola transformasi arsitektur kota Depok yang terjadi di kawasan sekitar kampus universitas dan pengaruhnya terhadap lingkungan fisiknya. Metode studi typo-morfologi perkotaan digunakan untuk menjawab masalah proses transformasi dan pola di lokasi penelitian dan masalah faktor-faktor yang mempengaruhi proses transformasi arsitektur kota di daerah tersebut dan pengaruhnya terhadap kualitas lingkungan fisik daerah tersebut. Penelitian ini mengungkap bahwa keberadaan kampus universitas memiliki efek ganda pada lingkungan fisik daerah sekitarnya. Perubahan unsur arsitektur kota yang tidak terkendali telah menyebabkan berbagai kondisi tidak aman dan menurunnya kualitas lingkungan fisiknya. Hasil penelitian dapat diterapkan untuk menghadapi perubahan lingkungan fisik di sekitar kampus universitas dan juga sebagai perbandingan dengan kota-kota lain dengan kasus serupa.Kata Kunci. Transformasi, arsitektur kota, kampus universitas, Depok.